ÃCIDO GIBERÃ‰LICO: ALGUMAS OBSERVAÃ‡Ã•ES SÃ”BRE UMA APLICAÃ‡ÃƒO EM CAPIM COLONIÃƒO - Freitas, Luis M. Martins de; McLung, A. C.; Quinn, L. R. (REVISTA DE AGRICULTURA, 2015)
ÃCIDO GIBERÃ‰LICO: ALGUMAS OBSERVAÃ‡Ã•ES SÃ”BRE UMA APLICAÃ‡ÃƒO EM CAPIM COLONIÃƒO